2004
DOI: 10.1177/153537020422900409
|View full text |Cite
|
Sign up to set email alerts
|

Fate of Bioterrorism-Relevant Viruses and Bacteria, Including Spores, Aerosolized into an Indoor Air Environment

Abstract: An aerosol physics test facility was used in a series of eight experiments to gather an integrated comprehensive broad base of data on the fate of surrogates of microorganisms that cause smallpox, plague, glanders, anthrax, and viral hemorrhagic fevers. The results are directly relevant to the public health issue of how to protect the occupants of buildings against bioterrorism. The test conditions were directly relevant to the indoor air environment situation, and the results can be generalized to buildings t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
12
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 6 publications
2
12
0
Order By: Relevance
“…Biosafety level 1 and 2 agents have been widely used as model organisms and recently Utrup and Frey (18) used several model organisms as surrogates of biological threat agents. These include Bacillus subtilis for B. anthracis (anthrax), E. coli for Variola major (Smallpox), Pseudomonas fluorescens for Burkholderia pseudomallei (melioidosis) (18).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Biosafety level 1 and 2 agents have been widely used as model organisms and recently Utrup and Frey (18) used several model organisms as surrogates of biological threat agents. These include Bacillus subtilis for B. anthracis (anthrax), E. coli for Variola major (Smallpox), Pseudomonas fluorescens for Burkholderia pseudomallei (melioidosis) (18).…”
mentioning
confidence: 99%
“…These include Bacillus subtilis for B. anthracis (anthrax), E. coli for Variola major (Smallpox), Pseudomonas fluorescens for Burkholderia pseudomallei (melioidosis) (18). The present paper reports results of an initial screen of a series of quaternary pyridinium oximes (19, 20) against a number of lower pathogenicity BSL-1 and 2 model organisms.…”
mentioning
confidence: 99%
“…Specifically, Bacillus atrophaeus has been used as a surrogate for B. anthracis in studies to develop methods to detect B. atrophaeus spores (8,52,55), to determine the effects of electric charge and field on the viability of airborne bacteria (34), to develop methods for viability assessment of Bacillus spores (31), to evaluate the effect of electric beam irradiation for inactivation of Bacillus spores in envelopes (16), and to investigate the effectiveness of decontamination methods against B. atrophaeus spores present on furniture (4,44). Serratia marcescens has been used as a surrogate for Yersinia pestis for examining the fate of pathogens in indoor air (56).…”
mentioning
confidence: 99%
“…Utrup and Frey found that 25 minutes following the initial aerosolisation, the levels of detectable MS2 had dropped by 28 % relative to the sample taken five minutes after aerosolisation (Utrup and Frey, 2004). This is a higher recovery than ours, however their methods and equipment differed, so realistically the results cannot be directly compared.…”
Section: Effect Of Elapsed Time On Ms2 As Detected By the Plaque Assamentioning
confidence: 42%